Les motivations à la maternité et leur impact sur le vécu des femmes - Bedard, Lucille; Spain, Armelle (Canadian Journal of Counselling and Psychotherapy, 2011)
This article proposes an original framework for understanding the motivations for motherhood by recognizing the complexity and idiosyncrasy of this motivational configuration while distinguishing between the concepts of intentionality and desire. Diverse motives are identified and grouped followed by a critical synthesis of psychoanalytic conceptualizations, economical models, and descriptive categories. From a review of the empirical literature, the impact of the motivations for motherhood on the experience of women is first globally considered and second, evaluated with regard to the physical symptomatology, psychological experience, mother/child bonding, and marital relationship. Finally, recommendations are suggested as to research, training, and practice in counselling.